Efficient Evaporative Cooling and Pronounced Heat Tolerance in an Eagle-Owl, a Thick-Knee and a Sandgrouse - Czenze, Zenon J.; Freeman, Marc T.; Kemp, Ryno; van Jaarsveld, Barry; Wolf, Blair O.; McKechnie, Andrew E. (Frontiers in Ecology and Evolution, 2021)
Avian evaporative cooling and the maintenance of body temperature (Tb) below lethal limits during heat exposure has received more attention in small species compared to larger-bodied taxa. Here, we examined thermoregulation at air temperatures (Tair) approaching and exceeding normothermic Tb in three larger birds that use gular flutter, thought to provide the basis for pronounced evaporative cooling capacity and heat tolerance. We quantified Tb, evaporative water loss (EWL) and resting metabolic rate (RMR) in the ∼170-g Namaqua sandgrouse (Pterocles namaqua), ∼430-g spotted thick-knee (Burhinus capensis) and ∼670-g spotted eagle-owl (Bubo africanus), using flow-through respirometry and a stepped Tair profile with very low chamber humidities. All three species tolerated Tair of 56–60°C before the onset of severe hyperthermia, with maximum Tb of 43.2°C, 44.3°C, and 44.2°C in sandgrouse, thick-knees and eagle-owls, respectively. Evaporative scope (i.e., maximum EWL/minimum thermoneutral EWL) was 7.4 in sandgrouse, 12.9 in thick-knees and 7.8 in eagle-owls. The relationship between RMR and Tair varied substantially among species: whereas thick-knees and eagle-owls showed clear upper critical limits of thermoneutrality above which RMR increased rapidly and linearly, sandgrouse did not. Maximum evaporative heat loss/metabolic heat production ranged from 2.8 (eagle-owls) to 5.5 (sandgrouse), the latter the highest avian value yet reported. Our data reveal some larger species with gular flutter possess pronounced evaporative cooling capacity and heat tolerance and, when taken together with published data, show thermoregulatory performance varies widely among species larger than 250 g. Our data for Namaqua sandgrouse reveal unexpectedly pronounced variation in the metabolic costs of evaporative cooling within the genus Pterocles.